2020
DOI: 10.1111/liv.14630
|View full text |Cite
|
Sign up to set email alerts
|

Bilirubin and bile acids in osteocytes and bone tissue. Potential role in the cholestatic‐induced osteoporosis

Abstract: Background and Aims: Osteoporosis is a common complication in patients with primary biliary cholangitis. Both bilirubin and lithocholic acid (LCA) result in detrimental effects on osteoblastic cells, and ursodeoxycholic acid (UDCA) counteracts these outcomes. However, there is no information on the consequences of these retained substances of cholestasis and sera from cholestatic patients in osteocytes. Methods: The impact of bilirubin, LCA, UDCA and serum from jaundiced patients on viability, differentiation,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 37 publications
0
11
0
Order By: Relevance
“…Interestingly, in the present study, LCA was significantly increased in the DIO group compared to the CON group. Previous studies have further demonstrated the deleterious consequences of LCA and bilirubin on osteoblastic cells (Ruiz-Gaspà et al, 2020a;Ruiz-Gaspà et al, 2020b). Low bone formation due to diminished osteoblast activity is the main cause of bone loss (Guañabens et al, 1990).…”
Section: Discussionmentioning
confidence: 98%
“…Interestingly, in the present study, LCA was significantly increased in the DIO group compared to the CON group. Previous studies have further demonstrated the deleterious consequences of LCA and bilirubin on osteoblastic cells (Ruiz-Gaspà et al, 2020a;Ruiz-Gaspà et al, 2020b). Low bone formation due to diminished osteoblast activity is the main cause of bone loss (Guañabens et al, 1990).…”
Section: Discussionmentioning
confidence: 98%
“…One obvious question based on our findings was if the increased levels of circulating bile acids would affect bone remodeling and potentially cause the decreased trabecular bone mass in PSC OPO patients. Indeed, there are previous studies suggesting that bile acids may influence the activity of bone remodeling cell types 19 , 20 , and an influence of the farnesoid X receptor (FXR), which functions as an intracellular bile acid sensor, on bone formation and resorption has been described 21 , 22 . Importantly, however, it has not been addressed yet, if the conjugated forms of bile acids would cause similar influences, which is a key question, since they are known to act through different receptor signaling complexes when compared to the unconjugated forms 23 .…”
Section: Discussionmentioning
confidence: 99%
“… 162 Furthermore, LCA and bilirubin were proven to have detrimental effects on the activity, differentiation and mineralization of osteoblasts, but these impacts could be neutralized by UDCA, suggesting that UDCA could be recognized as a potential therapeutic agent in osteoporotic patients with primary biliary cholangitis. 163 , 164 TUDCA, an FDA-approved hydrophilic BA for the treatment of chronic cholestatic liver disease, was proven to be a potent drug for ovariectomized mice at different concentrations. By administering TUDCA, more small beam structures in the distal femur were preserved, and other indices, such as total bone volume, bone mineral density, and bone volume percentage, were significantly improved compared to the control group.…”
Section: Bile Acid Network and Vascular Calcification-associated Dise...mentioning
confidence: 99%